2010
DOI: 10.1002/adem.201080020
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tetracycline Loading on the Surface Morphology and Biocompatibility of Films Made from P(3HB) Microspheres

Abstract: Tetracycline, an antibiotic used against a broad range of Gram positive and Gram negative bacteria was encapsulated in microspheres made of poly(3‐hydroxybutyric acid) P(3HB), a microbial biodegradable polymer isolated from Bacillus cereus SPV. The drug loaded microspheres were prepared using an oil emulsion technique and compressed uniaxially to produce films. Although the same fabrication conditions were used for preparing the drug loaded and unloaded microspheres, the presence of the drug changed the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[375] Microspheres of poly(3HB) have been tested for releasing the antibiotics rifampicin, [380] gentamicin, [381,382] and tetracycline. [383][384][385] In another study, poly(3HB-co-3HV) microspheres and microcapsules containing tetracycline were shown to be effective against many of the periodontal disease-related bacteria. Furthermore, poly(3HB-co-3HV) and poly(3HB-co-4HB) were used as antibiotic-loaded implantable rods for the local delivery of antibiotics (Sulperazone and Duocid, Sulbactam-cefoperazone) in chronic osteomyelitis therapy.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…[375] Microspheres of poly(3HB) have been tested for releasing the antibiotics rifampicin, [380] gentamicin, [381,382] and tetracycline. [383][384][385] In another study, poly(3HB-co-3HV) microspheres and microcapsules containing tetracycline were shown to be effective against many of the periodontal disease-related bacteria. Furthermore, poly(3HB-co-3HV) and poly(3HB-co-4HB) were used as antibiotic-loaded implantable rods for the local delivery of antibiotics (Sulperazone and Duocid, Sulbactam-cefoperazone) in chronic osteomyelitis therapy.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…PHA‐based nano/microspheres were also combined with inorganic materials in the design of composite DDS and drug‐eluting biomedical devices . Although mesoporous inorganic microparticles have been extensively studied as drug vehicles, such materials need to be chemically functionalised in order to achieve controlled drug release .…”
Section: Phas In Controlled Drug Deliverymentioning
confidence: 99%
“…Interestingly, gentamicin was released quicker compared with tetracycline, which was attributed to the interaction between tetracycline and HA. Drug‐eluting films for potential application in the treatment of skin infections were prepared by compression moulding of tetracycline‐loaded P(3HB) microspheres . The study did not include the characterisation of drug release.…”
Section: Phas In Controlled Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the attention of many researchers was focused on the chemical modification of PHAs and their copolymers in order to reach a stable chemical bond between the active substance and the matrix of the polymer or oligomer. These approaches have led to the development of controlled release systems for active substances [ 25 , 28 , 35 , 36 , 37 , 38 ]. To the best of our knowledge, there are no reports in the literature on the synthesis of composites based on tricalcium phosphates and polyhydroxyalkanoates with covalently attached molecules of (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%